La comprensión lectora en Braille y los procesos psicológicos en personas con discapacidad visual - Quispe Becerra, Fabiola (2022)
In recent years, the number of studies on the comprehension and speed of reading in braille has increased, from a cognitive approach, in order to improve the quality of life, and educational inclusion of people with visual disabilities. The objective of the systematic review was to identify the relationship of psychological functions in the process of reading comprehension in braille in people with visual disabilities. The study compilation was carried out according to the PRISMA guide (Page et al., 2021) located in the EBSCO, SCOPUS and PUBMED databases; where 10 investigations were collected, after excluding certain pre-established criteria. The result indicates the evidence that psychological processes are related to better reading comprehension performance in people with visual disabilities; however, there is no comprehensive view of the psychological processes for the development of reading. In conclusion, psychological functions have a positive relationship in the process of reading comprehension in braille in people with visual disabilities, but more research is required from a comprehensive approach.